2024
DOI: 10.1021/jacs.4c00860
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Reaction Network Drives Complex Population Dynamics in Oscillating Self-Reproducing Vesicles

Zhiheng Zhang,
Michael G. Howlett,
Emma Silvester
et al.

Abstract: We report chemically fueled oscillations of vesicles. The population cycling of vesicles is driven by their self-reproduction and collapse within a biphasic reaction network involving the interplay of molecular and supramolecular events. We studied the oscillations on the molecular and supramolecular scales and tracked vesicle populations in time by interferometric scattering microscopy and dynamic light scattering. Complex supramolecular events were observed during oscillations�including vesicle reproduction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…13 However, oscillators in which the properties and function of molecular assemblies are direct components of the oscillating reactions, as observed in biology, remain sparse. 14,15,16 Here, we developed synthetic cells endowed with active droplets. When the cells are constantly supplied with chemical energy, they produce active droplets that spontaneously oscillate in their organelle number, size, and position with a tunable period in the minute range.We found that the oscillations rely on a combination of a recently proposed size control mechanism, 17,18 and gravitationally induced fusion of droplets.…”
mentioning
confidence: 99%
“…13 However, oscillators in which the properties and function of molecular assemblies are direct components of the oscillating reactions, as observed in biology, remain sparse. 14,15,16 Here, we developed synthetic cells endowed with active droplets. When the cells are constantly supplied with chemical energy, they produce active droplets that spontaneously oscillate in their organelle number, size, and position with a tunable period in the minute range.We found that the oscillations rely on a combination of a recently proposed size control mechanism, 17,18 and gravitationally induced fusion of droplets.…”
mentioning
confidence: 99%